Integrated network pharmacology and experimental validation to investigate the therapeutic effects and mechanisms of SJZT on hypertensive nephropathy - Chen, Bin; Wang, Guanghui; Zhou, Jianbo; Han, Lina; Li, Li; Sun, Chengbin (Frontiers in Pharmacology, 2025)
IntroductionHypertensive nephropathy (HN) is a common complication of hypertension. Clinically, there is an urgent need for new HN treatment strategies. Sijunzitang (SJZT) is widely used in clinical practice, but its therapeutic effects and pharmacological mechanisms in the treatment of HN remain unclear.MethodsThe active components, key targets, and potential pharmacological mechanisms of SJZT in treating HN were investigated through mass spectrometry, network pharmacology, and molecular docking. Subsequently, we validated the therapeutic effects of SJZT and the potential mechanisms using an Angiotensin II (Ang II)-induced HN mouse model and primary renal fibroblasts in vitro.ResultsNetwork pharmacology identified 87 active components and 26 potential therapeutic targets of SJZT in treating HN, among which PPARγ, TNF, CRP, ACE, and HIF-1α were identified as key targets. Molecular docking demonstrated strong binding affinity between the core active components (Licoisoflavone B, Glabrone, and Frutinone A) and PPARγ. Animal experiments revealed that SJZT attenuated renal damage and extracellular matrix deposition in HN model mice. In vitro experiments revealed that SJZT suppressed Ang II-induced renal fibroblasts activation, as evidenced by reduced cell viability, α-SMA, and Collagen I expression. Mechanistically, SJZT alleviated hypertensive renal fibrosis through PPARγ upregulation in renal fibroblasts, subsequently inducing autophagy activation.ConclusionThis preclinical study establishes that SJZT ameliorates HN through a multi-component, multi-target, and multi-pathway mechanism. Key findings confirm that SJZT activates autophagy via PPARγ upregulation, which subsequently inhibits renal fibroblast activation and attenuates HN progression. These results provide a pharmacological foundation for the translational application of SJZT in HN treatment.